Outlook for the marine container shipping industry part III - environmental pressures : sulphur emissions reduction and its implications - Cai, Xingyi (2012)
Container shipping is of great importance in getting cargo moved around the globe, primary fast moving consumer goods, yet the concerns for environmental issues cannot be overlooked. A shipment of 1TEU from Shanghai to Hamburg is capable of producing 37kilograms of sulphur. This is an indication for growing attention needed in reducing sulphur emissions which explains the revision of MARPOL Annex VI into more stringent sulphur regulations when trading within and outside the SECA. This report aims to discuss the implications of sulphur emissions reduction pressure on container shipping companies and finally concluding on the short term and long term outlook of the marine container shipping industry in this aspect.